Additional Assessment of Fecal Corticosterone Metabolites Improves Visual Rating in the Evaluation of Stress Responses of Laboratory Rats - Tina Kroll; Nikola Kornadt-Beck; Angela Oskamp; David Elmenhorst; Chadi Touma; Rupert Palme; Andreas Bauer (Animals, 2021)
Since animal experiments cannot be completely avoided, the pain, suffering, and distress of laboratory animals must be minimized. To this end, a major prerequisite is reliable assessment of pain and distress. Usually, evaluation of animal welfare is done by visual inspection and score sheets. However, relatively little is known about whether standardized, but subjective, score sheets are able to reliably reflect the status of the animals. The current study aimed to compare visual assessment scores and changes in body weight with concentrations of fecal corticosterone metabolites (FCMs) in a neuroscientific experimental setup. Additionally, effects of refinement procedures were investigated. Eight male adult Sprague-Dawley rats underwent several experimental interventions, including electroencephalograph electrode implantation and subsequent recording, positron emission tomography (PET), and sleep deprivation (SD) by motorized activity wheels. Additional 16 rats were either used as controls without any treatment or to evaluate refinement strategies. Stress responses were determined on a daily basis by means of measuring FCMs, body weight, and evaluation of the animals’ welfare by standardized score sheets. Surgery provoked a significant elevation of FCM levels for up to five days. Increases in FCMs due to PET procedures or SD in activity wheels were also highly significant, while visual assessment scores did not indicate elevated stress levels and body weights remained constant. Visual assessment scores correlate with neither changes in body weight nor increases in FCM levels. Habituation procedures to activity wheels used for SD had no impact on corticosterone release. Our results revealed that actual score sheets for visual assessment of animal welfare did not mirror physiological stress responses assessed by FCM measurements. Moreover, small changes in body weight did not correlate with FCM concentration either. In conclusion, as visual assessment is a method allowing immediate interventions on suffering animals to alleviate burden, timely stress assessment in experimental rodents via score sheets should be ideally complemented by validated objective measures (e.g., fecal FCM measured by well-established assays for reliable detection of FCMs). This will complete a comprehensive appraisal of the animals’ welfare status in a retrospective manner and refine stressor procedures in the long run.